BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TB PARU - Sitorus, Jenti; Latumenase, Rony A.; Nordianiwati, Nordianiwati; Kristina, Yunita; Kaluku, Suratno (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Tuberculosis (TB) is a contagious infectious disease caused by Mycobacterium tuberculosis bacteria that can cause death. One of the risk factors for TB is ventilation and lighting in homes that are not in accordance with health requirements. Data from Puskesmas Tapung II in 2022 amounted to 32 people and it was known that 29.43% of houses were not included in the category of healthy homes. This study aims to determine several factors associated with the incidence of pulmonary TB in the Tapung II Puskesmas working area. This type of research is quantitative with a cross sectional approach. The research was conducted in April 2023 in the Tapung II Health Center working area. The research sample amounted to 33 respondents who were taken using the total sampling technique. Data collection tools using a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed that there was a relationship between house ventilation (p value 0.013) and house lighting (p value 0.005) with the incidence of pulmonary TB. This study recommends patients with pulmonary TB to maintain the cleanliness of the home environment and arrange home ventilation properly so that sunlight and fresh air can enter the house, maintain behavior not to spit or dispose of phlegm carelessly and cover the mouth with a tissue / cloth when coughing or sneezing to prevent transmission to others.Keywords: Tuberculosis, Lighting, Ventilation.